SOME EFFECTS OF CORRECTIVE FEEDBACK ON STUDENTS' WRITING - nirwana ar (Universitas Islam Negeri Alauddin Makassar, 2020)
Several researchers have investigated the effects of corrective feedback (C.F.) Several researchers have investigated the effects of corrective feedback (C.F.) on learners' linguistic competence. Still, there was an opportunity to research some effects of WCF on students' linguistic errors by comparing six types of C.F. (direct, indirect, metalinguistic, reformulation, focused, and unfocused C.F.). Single-subject experiment design with alternating treatment design was beneficial in assessing the relative effectiveness of six types of C.F. Linguistic errors categories on vocabulary, language use and mechanics were targeted in C.F. The results of research findings for five weeks study and six students for one group or thirty-six students in the Muhammadiyah University of Makassar showed that direct C.F. had the most significant effect in reducing students' linguistic error and improving students' writing quality in vocabulary, language use and mechanics than the other types of C.F. and direct C.F. also could be suggested for using long-term to the teacher and students at a low intermediate proficiency level.